Can Brain-derived Neurotrophic Factor (BDNF) Mimetics be a Way Out for Neurodegenerative Diseases? - Korkmaz, Orhan T. (Current Pharmaceutical Design, 2023)
Neurodegenerative diseases are chronic and progressive disease groups characterized by the decline of neural transmission because of the loss of structure and function of neurons. Although there is currently no effective treatment for neurodegenerative diseases, new treatment strategies need to be developed urgently. Among neurotrophins, BDNF has been extensively investigated, and it has emerged as an important regulator of synaptic plasticity, neuronal survival, and differentiation. Changes in BDNF levels and signaling pathways have been identified in several neurodegenerative diseases. Moreover, promising results have been obtained for BDNF in many experimental studies on animal models. In addition, BDNF serves as a crucial molecular target for developing drugs to treat neurological diseases. However, several pharmacokinetic difficulties have limited its use in clinical practice, such as its inability to cross the blood-brain barrier, short half-life, and potential adverse effects. To avoid these difficulties, several approaches have been explored, but they have led to disappointing results. One way to overcome the limitations of BDNF may be with mimetic molecules that can effectively stimulate the receptors it has an affinity with and thus activates BDNF pathways. In this perspective article, an evaluation of the efficacy of different BDNF mimetics against neurodegenerative diseases was made.
Keywords: BBB